The Effect Of Price Through Product Quality On Purchase Decisions Moderated By Customer Experience - Wiyatiah, Ambar Sri; Soraya, Nabila; Pitaloka, Okka Chandra; Inayah, Yuni (Lentera Ilmu Nusantara, 2024)
The economy in today's era of globalization has fierce competition, especially in the business world, where each company moves to continue to make products that are mainly to meet what is needed by consumers and companies are always innovating to make products that are different from before and from competitors and strive to be superior to other products. This study was conducted with the aim of analyzing the price variable as an independent variable, the purchase decision variable as a dependent variable, the Product Quality variable as a mediation variable, and the Customer Experience variable as a moderation variable. This study uses the method of distributing questionnaires to respondents directly who are consumers of Pepsodent toothpaste products. This type of research is quantitative research. The data processed is primary data obtained from the results of the questionnaire distribution using a simple random sampling technique. From 100 respondents, a sample of 102 respondents was obtained. The data analysis was used using the Smart PLS program. The analysis carried out in this study uses a hypothesis with a partial test The results of the analysis research, the indicators in this study are valid. Price (X) has no effect on consumer Purchase Decision (Y), Price (X) has a positive effect on Customer Experience (Z), Customer Experience (Z) has a positive effect on Purchase Decision (Y), product quality (M) passed by price (X) has a significant positive effect on purchase decision (Y), and Price (X) strengthened by Customer Experience (Z) has a significant positive effect on purchase decision (Y). The results of this research can be used to design the right pricing strategy, product quality and Customer Experience to improve consumer purchasing decisions.